ISLAMIC FINANCE MODE IMPACTS ON ECONOMIC DEVELOPMENT AND FINANCIAL SUSTAINABILITY IN PAKISTAN - MUHAMMAD SAEED IQBAL; DR. SOFI MOHD FIKRI (Hamdard Islamicus)
The research investigates the association between Islamic bank (IB) operations and economic development in Pakistan. Specifically, it questions whether Islamic banks are essential for economic development and how their operations contribute to financial sustainability. The study investigates the link between Islamic banking practices and financial sustainability, focusing on GDP and Z-score. It identifies the impact of Islamic financing modes on economic development. Cross-sectional data set research employing a quantitative methodology. Data was collected from five Islamic banks in Pakistan, covering 2018 to 2022. Pearson regression analysis was utilized to quantify the relationships between GDP and the Z-score while focusing on different Islamic financing structures. IjÉrah and MurÉbaÍah (مرابحہ) modes are negatively linked with GDP, indicating a significant correlation coefficient of 0.79 between financial methods and GDP. In addition, the assessment shows and negative and significant correlation between all forms of payment except MurÉbaÍah, which has a Z-score of 0.94. But the correlation among Z-score and MurÉbaÍah and MuÌÉrabah (المضاربة) is insignificant in all cases. Regression tests provide two models. Overall, the results suggest a strong relationship between the use of all forms of payment, except for MurÉbaÍah, which is independent of Z-score. Therefore, it can be concluded that MuÌÉrabah has no significant relationship with the Z score. This research explores the link between Islamic financial structures and economic development in Pakistan. In addition to quantitative methods, Islamic banking products are used. It offers valuable information for policymakers and stakeholders.